Aerodynamics of a knuckleball - Watts, R. G.; Sawyer, E. (American Journal of Physics, 1975)
The nature of the forces causing the erratic motion of a knuckleball has been investigated by measuring the lateral force on a baseball in a wind tunnel. We have identified two possible sources of a lateral force imbalance that can give rise to the observed erratic changes in the direction of a knuckleball as it moves through the air. One of these results because the nonsymmetrical location of the roughness elements (strings) gives rise to a nonsymmetrical lift (lateral) force. A very slowly spinning knuckleball will have imposed upon it a lateral force that changes as the positions of the strings change. A knuckleball whose spin is identically zero has a constant lateral force unless a portion of the strings is precisely at a location where boundary layer separation occurs. If this happens, the point of boundary layer separation switches alternatively from the front to the rear of the strings, shifting the wake from one position to another, and thereby giving rise to a second possible alternating force imbalance. A two-dimensional analysis of the trajectory of the baseball indicates that the measured force can cause a deflection of the baseball's trajectory of more than a foot. An effective knuckleball should be thrown so that it rotates substantially less than once on its path to home plate.